Exploring the causal link among statin drugs and the osteoarthritis risk based on Mendelian randomization research - Chen, Wenjie; Sun, Zhi; Xiong, Xinhai; Tan, Haitao; Hu, Junhao; Liu, Chenrui; Chen, Cheng (Frontiers in Genetics, 2024)
Purpose: Statins may have a protective effect against osteoarthritis (including knee osteoarthritis and hip osteoarthritis), however the link between statins and osteoarthritis risk is incompletey established. The study purpose was to explore the relationship among statins and osteoarthritis risk through Mendelian randomization analysis using pooled information from a large population-wide genome-wide association study (GWAS). Methods: Statin-related SNPS were obtained from FinnGen's latest 9th edition database, and osteoarthritis, osteoarthritis in knee and hip data were acquired from the IEU Open GWAS, the UK Biobank and Arthritis Research UK Osteoarthritis Genetics (ArcOGEN) database. Inverse variance weighting method is an important analysis method to estimate the causal effect. Weighted median method, simple median method, weighted median method and MR-Egger regression were employed to supplement the explanation. Odds ratios and 95%CI were used to evaluate the causal association among statins and the osteoarthritis risk, osteoarthritis in knee, and osteoarthritis in hip. Secondly, sensitivity analysis was carried out to validate the results reliability. Cochran's Q was employed to test heterogeneity, MR-Egger intercept was employed to test whether horizontal pleiotropy existed and single nucleotide polymorphism with potential influence was determined by the one-method analysis. Results:⑴ The results of inverse variance weighted method showed that genetically predicted statin was associated with osteoarthritis (OR=0.998, 95%CI: 0.996-0.999, P=0.01), knee osteoarthritis (OR=0.964, 95%CI: There was a negative causal relationship between 0.940-0.989, P=0.005) and the hip osteoarthritis risks (OR=0.928, 95%CI: 0.901-0.955, P=4.28×10-7).⑵MR-Eggerintercept analysis did not detect potential horizontal pleiotropy (osteoarthritis: P=0.658; Knee osteoarthritis: P=0.600; Hip osteoarthritis: P=0.141). ⑶The findings provide evidence that statins reduce the osteoarthritis risk, osteoarthritis in knee and osteoarthritis in hip as described in observational studies, and the specific mechanisms by which statins treat osteoarthritis require further investigation. Conclusion: The results of this study at the genetic level, reveal a negative causal association between statins and osteoarthritis, and this causal association is also present in knee osteoarthritis and hip osteoarthritis. This study provides the statins in evidence against a potential in the treatment of osteoarthritis, prompt the future in the clinical treatment of osteoarthritis can consider improving statins start and compliance.